Modeling subgrain structure evolution during heat treatment (Fracture and Structural Integrity, 2026)
This paper presents a novel modification of the multilevel statistical model for describing the subgrain boundary migration that can explicitly account for the topology of subgrain structures in the form of Laguerre polyhedra. The evolution of a representative volume of subgrains during annealing in the temperature range  200 - 340 °C  after plastic deformation taking into account competing recovery processes like coalescence and subgrain boundary migration is modeled. The material used in this study is the nickel-based superalloy Inconel 718 with complex hierarchical structure and specific phase composition. The results of modeling the changes in a polyhedral subgrain structure under recovery are presented. The contribution of subgrain coalescence and migration processes to recovery is evaluated. The abnormal growth of subgrains is described by the model, the conditions of its occurrence and implementation are defined. The calculated data demonstrate good agreement with experimental results.
Keywords: Static recovery; Subgrain structure; Subboundary migration; Subgrain coalescence; Recrystallization nuclei; Nickel-based superalloy Inconel 718